Узагальнена модель Дікке як інверсна нелінійному рівнянню Шредінгера інтегровна динамічна система - Самуляк, Р.В. (Український математичний журнал, 1995)
We prove that a dynamical system obtained by the space-time inversion of the nonlinear Schrödinger equation is equivalent to a generalized Dicke model. We study the complete Liouville integrability of the obtained dynamical system.